Determination of Factors Affecting International Students’ Satisfaction Levels Using CHAID Analysis - İbrahim Hakan Göver; Asim Mustafa Ayten (Üniversite Araştırmaları Dergisi)
Internationalization has recently been a core element for higher education institutions (HEIs) worldwide. Various components provide internationalization in HEIs. However, international students stand out from the others due to providing numerous benefits to host countries. Therefore, HEIs around the world seek to increase the number of international students and their satisfaction levels. This study, inspired from the importance of international students, seeks to determine the factors affecting the satisfaction levels of international students who study at a Turkish state university. To this end, an on-line survey consisting of 25 questions were administered to a total of 330 international students studying at Middle East Technical University (METU). Survey data were evaluated using the CHAID (Chi-Squared Automatic Interaction Detection) analysis. The findings of the analysis indicated that the international students’ implications, study degree and gender played a major role in their satisfaction levels. Considering these influential factors determined by the CHAID analysis will contribute to the internationalization strategies which is developed to attract more international students to HEIs.